Paget’s disease of male breast, a rare but rising ailment - Yadav, Randhir Sagar; Shrestha, Shumneva; Singh, Prabesh Bikram; Sharma, Sadikshya; Nepal, Bikash; Sayami, Prakash (Journal of Society of Surgeons of Nepal, 2017)
Male breast cancer constitutes less than 1% of all breast carcinomas whereas Paget’s disease accounts for less than 1% of entire breast cancers. Unawareness and misdiagnosis lead to delayed presentation at a higher grade making the prognosis worse than females. Genetics and hormonal factors are strongly linked to its occurrence. Investigations, diagnosis, staging and management strategies for male breast cancers are concluded from studies done in female cases. We present a case of a 65 years literate gentleman who presented with fungating right breast mass with bleeding ulcer who underwent modified radical mastectomy, chemotherapy, radiotherapy and hormonal therapy.